2018
DOI: 10.3906/tar-1702-59
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morphological, chemical, and sensory characteristicsof raspberry cultivars grown in Bosnia and Herzegovina

Abstract: IntroductionAccording to the Agency for Statistics of Bosnia and Herzegovina (www.bhas.ba), raspberry production in Bosnia and Herzegovina (B&H) increased from 9433 t to 13,631 t by 2015, followed by an increase in yield that increased from 5 t/ha to 8.1 t/ha. During this period, a decline in production was recorded in 2012 due to the heavy floods that hit B&H. Production of raspberries and other berries is very important from an economic point of view, i.e. from the aspect of agricultural development (Ercisli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
(43 reference statements)
7
27
0
Order By: Relevance
“…The total flavonoid content, (116.79 to 204.42 mg CE/100 g fresh weight) compared to raspberries in Turkey (Sariburin et al, 2010), Brasil (Rios de Souza et al, 2014), and Serbia (Cetojević-Simin et al, 2015), was in the more than average range. However, interestingly, the total monomeric anthocyanin content was lower than values reported elsewhere (6.30 to 11.63 mg C3GE/100 g frozen weight) (Poledica et al, 2012;Alibabić et al, 2018). The dry matter content was higher in Meeker and Tulameen than in Willamette, in both experimental years, which is in accordance with the findings of Leposavić et al (2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The total flavonoid content, (116.79 to 204.42 mg CE/100 g fresh weight) compared to raspberries in Turkey (Sariburin et al, 2010), Brasil (Rios de Souza et al, 2014), and Serbia (Cetojević-Simin et al, 2015), was in the more than average range. However, interestingly, the total monomeric anthocyanin content was lower than values reported elsewhere (6.30 to 11.63 mg C3GE/100 g frozen weight) (Poledica et al, 2012;Alibabić et al, 2018). The dry matter content was higher in Meeker and Tulameen than in Willamette, in both experimental years, which is in accordance with the findings of Leposavić et al (2013).…”
Section: Discussionsupporting
confidence: 90%
“…All 3 cultivars in both experimental years (Table 3) had extremely high total phenolic contents (1578.66-2301.86 mg GAE/100 g fresh weight ), which is a result that has rarely been recorded in the literature (Pantelidis et al, 2007;De Ancos et al, 2000;Poledica et al, 2012;Orzel et al, 2016). Literature values for TPC are generally up to 500 mg GAE/100 g fresh weight (Milivojević et al, 2011;Alibabić et al, 2018). Many studies have shown that fruit characteristics are influenced by factors such as climate conditions, altitude, soil characteristics, ripeness at harvest time, irrigation and other cultural practices, and cultivar characteristics, which explain differences across experiments (Milivojević et al, 2011;Leposavić et al, 2013;Natić et al, 2015;Andrianjaka-Camps et al, 2016;Alibabić et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Horticultural plants ha ve been used for therapeutic, religious, cosmetic, nutritional, and beautification purposes since ancient times and humanity of all civilizations and culture are familiar with their usage (Alibabic, Skender, Orascanin, Sertovic, & Bajric, ; Alp et al, ; Galiana‐Belaguer, Ibanez, Cebolla‐Cornejo, & Rosello, ). The unique beauty of flowers and subtle fragrancy convey a message guaranteed to elicit delight.…”
Section: Introductionmentioning
confidence: 99%